1995
DOI: 10.1042/bj3120287
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol 3-phosphate-induced ATP production in intact mitochondria from pancreatic B-cells

Abstract: A bioluminescent method is presented that allows monitoring of ATP production from mitochondria corresponding to one islet of Langerhans per sample. In mitochondria from ob/ob mice Ca2l stimulates the ATP production in the presence of L-glycerol 3-phosphate (GP) by reducing the K,m for GP by one order of magnitude to about 3 mM. Maximal ATP production in the presence of Ca2l (200 nM) is obtained at 10 mM GP. The free calcium concentration required to reach half-maximal stimulation (Ko.,c2+) depends on the GP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…233,269,323,326,427,459). Maechler et al (323) reported that methyl-pyruvate (rather than pyruvate) supported matrix Ca 2ϩ accumulation and insulin secretion from ␣-toxin-permeabilized INS-1 cells (323).…”
Section: Permeabilized Cell Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…233,269,323,326,427,459). Maechler et al (323) reported that methyl-pyruvate (rather than pyruvate) supported matrix Ca 2ϩ accumulation and insulin secretion from ␣-toxin-permeabilized INS-1 cells (323).…”
Section: Permeabilized Cell Preparationsmentioning
confidence: 99%
“…The paucity of respiratory studies on isolated ␤-cell mitochondria or permeabilized cell preparations, perhaps exacerbated by the apparent difficulty of such preparations to utilize complex I, has meant that such studies are virtually nonexistent, and it is surprisingly difficult to locate any publications employing isolated mitochondria, or permeabilized ␤-cells, exposed to these substrates. One exception was the use of luciferase to detect ATP generation by a heterogeneous preparation of mito-chondria isolated by centrifugation from ob/ob mouse islets (233,289 Ϫ1 for pyruvate, although in the apparent absence of added CoA or carnitine it is difficult to see how the fatty acids could be activated.…”
Section: E Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mitochondrial fraction from AQP3 ϩ/ϩ mouse epidermis was obtained as described previously (7). Mitochondrial ATP production was assayed as described previously (13).…”
Section: Mice Aqp3mentioning
confidence: 99%
“…Large islets with a high content of β-cells ( 90 % ; [16]) can be isolated, and the mitochondria obtained may be regarded to represent pure β-cells. Mitochondria were prepared as described in [17]. Comparative studies with mitochondria from lean mice demonstrated a normal function of ob\ob mice mitochondria [17].…”
Section: Isolation Of Mitochondriamentioning
confidence: 99%